Earthflight. The complete series [videorecording (DVD)] - Downer, John; Downer, John; Downer, John; Tennant, David, 1971- (BBC Earth, 2014)
Narrated by David Tennant, this documentary focusing on the flight of birds was filmed over four years and forty countries with help from camera-carrying birds, drones, paragliders and remote-control microflight planes.